Practical pricing and the car park - Guadix, José (Henry Stewart Talks, 2009)
Application of revenue management in the car park sector, Forecast demand, Optimizing spaces distribution, Parking inventory control, Group of subscribers, Computational experiences, Incomes, efficiency and occupation